Interferon-α and pericardial injury: a case report and literature review. Issue 1 (16th April 2014) - Hakim, Fayaz A; Singh, Sujata; Pandit, Anil; Alegria, Jorge R; Camoriano, John; Stanton, Melissa L; Mookadam, Farouk
Abstract : Interferon- α (IFN-α) alone or in combination with other chemotherapeutic agents has been used in the management of many malignant and non-malignant conditions. Pericarditis with or without pericardial effusion has been reported with IFN-α therapy, and available literature is limited to case reports. Pericardial constriction after interferon use has not been described in the published literature to date. We performed a systematic review of literature to address the demographic features, clinical presentation, diagnosis, treatment and outcome of interferon-related pericardial injury.